AQUATIC ETHICS SCHOOL: LEARNING TO PROTECT THE COASTAL ENVIRONMENT AT SMP NEGERI 6 BOZIHONA, IDANOGAWO DISTRICT - Anggela Opsi Yantri Gulo; Andika Taufik; Asni Putri; Sani Waruwu; Cevin Winata Mendrofa; Destalenta Trisna Laoli; Darwis Triadi; Eduard Moris Lase (Jurnal Abdisci, 2026)
Background. Coastal areas are among the most productive ecosystems on Earth, yet they are also among the most exposed to human carelessness, particularly the steady inflow of plastic waste. Aims. This activity was carried out to build the knowledge, attitude, and moral responsibility of young people toward coastal sustainability through the "Aquatic Ethics School: Learning to Protect Coastal Environments" program, held on 18 June 2026 at SMP Negeri 6 Idanogawo, Nias Regency, North Sumatra. Methods. The program combined interactive talks, small-group discussion, an open Q&A session, and a closing commitment declaration written and read by the students themselves. Before the session, most participants could not clearly connect everyday habits with the condition of the coast near their school; afterward, they were able to explain microplastic formation, the logic behind Reduce-Reuse-Recycle, and where they personally fit into the problem. Conclusion. The enthusiasm shown during discussion, together with the willingness to sign the commitment declaration, suggests that ethics-based environmental education can move students from passive awareness toward a felt sense of responsibility for the coastline they live beside.